The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1001/jamapediatrics.2018.1024
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Consequences of a 2013 Measles Outbreak in New York City

Abstract: IMPORTANCE Internationally imported cases of measles into the United States can lead to outbreaks requiring extensive and rapid control measures. Importation of measles from an unvaccinated adolescent in 2013 led to what has been the largest outbreak of measles in New York City, New York, since 1992. OBJECTIVE To describe the epidemiology and public health burden in terms of resources and cost of the 2013 measles outbreak in New York City. DESIGN, SETTING, AND PARTICIPANTS This epidemiologic assessment and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…80 The unnecessary economic burden for society caused by low vaccine confidence was clearly shown by evaluating the economic burden of several past measles outbreaks. [93][94][95][96][97] In 2011, the US experienced 16 measles outbreaks and the total economic burden on public health institutions was estimated to be in the range of USD 2.7-5.3 million. 98 In 2008, a measles outbreak in San Diego, that originated from an intentionally unvaccinated seven-year-old boy, cost the community nearly USD 177,000, which included medical care provision to the confirmed cases, tracking of suspected cases, quarantining people, enhancing surveillance, and following up an infected infant and related contacts in Hawaii.…”
Section: Economic Consequences Of Low Vaccine Confidencementioning
confidence: 99%
“…80 The unnecessary economic burden for society caused by low vaccine confidence was clearly shown by evaluating the economic burden of several past measles outbreaks. [93][94][95][96][97] In 2011, the US experienced 16 measles outbreaks and the total economic burden on public health institutions was estimated to be in the range of USD 2.7-5.3 million. 98 In 2008, a measles outbreak in San Diego, that originated from an intentionally unvaccinated seven-year-old boy, cost the community nearly USD 177,000, which included medical care provision to the confirmed cases, tracking of suspected cases, quarantining people, enhancing surveillance, and following up an infected infant and related contacts in Hawaii.…”
Section: Economic Consequences Of Low Vaccine Confidencementioning
confidence: 99%
“…Suboptimal vaccination coverage was identified as the key causative factor, with 87% of the affected individuals being unvaccinated. Similarly, a recent epidemiologic assessment of the 2013 measles outbreak in New York City indicated that 78% of the infected individuals were "unvaccinated owing to parental refusal or intentional delay" (2). The direct cost of the outbreak to the New York City Department of Health and Mental Hygiene was estimated as $394,448 and a total of 10,054 working hours.…”
Section: Accepted Manuscript Backgroundmentioning
confidence: 99%
“…Without the implemented vaccination campaigns, the severity of the measles outbreak-including number of infections, hospitalizations, and severe infections needing intensive care-would be about 10 times worse than observed ( Table 2). These estimates, however, did not include the long-term health impacts on affected individuals, particularly young children (10,19,20), nor the enormous economic burdens (13,21,22).…”
Section: Discussionmentioning
confidence: 99%